Late Developed Unusual Nasal Involvement of Postoperative Maxillary Cyst Following Maxillary Sinus Augmentation: A Case Report - Won-Bae Park; Hyun-Chang Lim (Applied Sciences, 2021)
Postoperative maxillary cyst (POMC) is a benign expansive cystic lesion of the maxilla generally related to invasive maxillary surgeries or trauma. POMC can also develop after maxillary sinus augmentation (MSA), but many dentists are not well-aware of such complication of MSA. A 56-year-old male patient had undergone bilateral MSA. After 18 years, the patient reported painless swelling on the left palate. On the panoramic radiographs, no specific findings were found, but a large unilocular lesion was detected at the medial side of the previous augmentation of the left maxillary sinus on cone-beam computed tomographic examination. The lesion expanded medially and downward to destruct the medial wall of the maxillary sinus and palatal bone. Medial expansion of the lesion also reached the nasal septum and inferior meatus. Due to the extent and the location, the lesion was hard to manage using an intraoral surgical approach. The patient was then referred to an otolaryngologist in a university hospital. Endoscopic marsupialization was performed under general anesthesia. Previous augmentation and dental implants could be maintained during the marsupialization. The removed tissue sample revealed respiratory epithelium with inflammatory cell infiltration, confirming that the lesion was a postoperative maxillary cyst (POMC). There has been no recurrence of POMC to date. POMC is a rare postoperative complication of maxillary sinus augmentation, but clinicians should be aware of the possibility of POMC and the necessity of regular radiological monitoring.